INCREASING RISK OF HEAVY METAL CONTAMINATION IN SILVOFISHERY PONDS - Endah Dwi Hastuti (BIOTROPIA, 2021)
This research aimed to determine the concentration of organic matter, Pb, and Cd found in a silvofishery pond, to assess the toxicity level, to analyze changes in their concentrations within a one-year period, and to analyze the correlation between these concentrations and their changes. The research was conducted through five field observation activities and laboratory analyses from May 2016 to July 2017. Data were analyzed using ANOVA and correlation tests. The concentration of organic matter, Pb, and Cd increased across all five observations. Throughout the research, the concentration ranges were 1.60–3.30 mg/kg for organic matter, 3.130–8.230 mg/kg for Pb, and 1.089–2.820 mg/kg for Cd. In all observations, the toxicity assessment showed that Cd concentration in the sediment exceeded the standards recommended by the US EPA (≤1.0 mg/kg) and ANZECC & ARMCANZ (≤1.5 mg/kg), while Pb concentration remained within the safe limits (≤21 mg/kg and ≤50 mg/kg, respectively). Moreover, the concentration and accumulation of Pb and Cd were strongly correlated, indicating the possibility of originating from the same pollutant sources. Therefore, a better management plan is recommended to prevent heavy metal accumulation in silvofishery ponds, including arranging mangrove plants along inlet canals and implementing periodic pruning to prevent heavy metals from re-entering the environment through litter fall.